PERTAMBAHAN BOBOT BADAN HARIAN SAPI BRAHMAN CROSS PADA BOBOT BADAN DAN FRAME SIZE YANG BERBEDA - Ardhina Firdausi; T. Susilawati; M. Nasich; Kuswati Kuswati (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2012)
This research was conducted at PT. Widodo Makmur Perkasa Feedlot onAugust until October 2011. The purpose is to assess average daily gain of Brahmancross with frame sizetype(M andL) anddifferentbodyweights(<300 kg, 300-350kg,and>350 kg) and theinteractionbetween theframe sizeanda differentbodyweights.Thematerialsused for this research were 3052 head SteerBrahmanCrosscattle with initialbody weights250 kg-380 kg. This research was using study casus. data obtained wassecondary data. The obtained data was analyzed using Completely Random Design(CRD) inbalanced factorial.The result showed that frame size has significant effect(P<0,01) on Brahman cross steer average daily gain. The average daily gain is 1.15 ±0.367 kg for M frame size group and 1.3 ± 0.354 kg for L frame size group. Initialbody weight was also has a significant effect on Brahman cross steer average dailygain. The average daily gain of <301; 301-350; and >350 group were 1.329±0.366;1.22±0.348; and 1.13±0.357 kg. The interaction between frame size and initial bodyweight give significant effect on Brahman cross steer daily gain. The gain of <301kg ofinitial body weight group with L framesize is 1.34 kg/day and M frame size is 1.29kg/day. The gain of 301-350kg of initial body weight group with L frame is 1.31kg/day. And the gain of >350kg of initial body weight group with L frame size is 1.21kg/day and M frame size is 0.93 kg/day.Key word : Average Daily Gain, Brahman cross, Frame size, Initial Body Weight